(untitled) (Journal of Plant Disease Sciences, 2018)
Betelvine or ‘Pan’ (Piper betel L) is a perennial dioecious, shade loving root climber native of Malaysia is grown in India since ancient times. In Maharashtra, the cultivation of betel vine is restricted to an area of about 2,300 hectares including Sangli, Satara, Kolhapur, Thane, Pune, Nashik, Jalgaon, Buldhana, Dhule, Aurangabad, Akola, Amravati and Nagpur districts. The shady and moist atmosphere also favours the development of many diseases, especially root rot complex that greatly affects the growth of plants resulted in heavy losses to the farmers. Though the complex disease is reported to cause due to different fungal agents, prominent among them are Fusarium solani, Rhizoctonia bataticola and Sclerotium rolfsii. Patil et al. (1986) reported that betelvine was seriously attacked by root rot disease due to Sclerotium rolfsii, Fusarium spp., Rhizoctonia bataticola, Phytophthora and Pythium spp. during rainy season in Vidarbha region.